Attractors of university students' agency development stages - Alexander V. Kaptsov; Ekaterina V. Nekrasova (Saratov State University, 2021)
The relevant problem of social educational psychology is to identify states of self-organization and self-development of students' psychological traits in the academic group. One of the possible ways to solve the problem is to use the mathematical theory of dynamic systems to determine the attractors of the development stages of university students' agency. The purpose of the study presented in the article is to substantiate application of the theory of complex dynamic systems in modeling development stages of university students' agency. Hypothesis of the study: the theory of complex dynamic systems is applicable to modeling the development stages of university students' agency. Approbation of the theory of dynamical systems was carried out in the course of a longitudinal study in four groups of 1st to 4th year full-time students (N = 79; M = 19.6; SD = 2.4 years; 100% women). The study revealed that the development stages of university students' agency have one stable stationary state. The interval between two measurements was 28 weeks. The most common attractors are found in the "learner" and "master" stages. We revealed two stable states in the stages in the second-year students' group. The stages indicate presence of micro groups with different levels of manifestation of development stages of agency, which are characterized by the phenomenon of self-organization in the academic group. The applied aspect of the study is to create a dynamic model of the stages of university students' agency development in a separate academic group. The research showed prospects of applying the dynamic systems theory combined with the ecopsychological approach.